Structural characteristics and topographic preferences of Polylepis rugulosa stands according to slope exposure in the most arid region of the southwestern Peruvian Andes. - Gutierrez Flores, Ivon Rocio; Sanga Franco, Marianela; Ticona Quispe, Pedro (BOSQUE, 2023)
Polylepis forests are among the least studied and most threatened in the world, particularly P. rugulosa, due to the high pressure it has historically suffered from high Andean populations. Although the 28 species of the genus have similar ecological niches, each species has certain preferences for solar radiation, temperature and moisture, which are affected by topographic factors. We analyzed the structural differences and the effects of topographic factors in stands of P. rugulosa on east and west facing slopes in the most arid region de Peru. The evaluation was carried out in 20 x 30 m plots in three watersheds in the Tacna region, located between 3800 and 4200 m a.s.l. Density and basal area were higher on the west facing slopes. The other variables (cover, height, diameter) were not different, indicating that despite the greater recruitment success on the west facing slopes, the development would be similar between both exposures. The topographic variables that showed some effects were vertical flow distance, overland flow distance, slope, morphometric protection index and topographic wetness index. Likewise, it was observed that on the east facing slopes, there was a greater dependence of the topographic factors on the structural variables. This study highlights the importance of some topographic factors in the development of Polylepis forests, and that these effects change with the slope exposure.